Early-onset neurolupus: A challenge for pediatricians - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Systemic lupus erythematosus (SLE) is a challenge for pediatricians due to the heterogeneity of its clinical manifestations and the rarity of the disorder in this age group. Neuropsychiatric SLE (NPSLE) was defined especially in adult patients and the clinical course of this manifestation is still not clearly defined in the pediatric age group. We, here report a five-year old girl presenting with extensive maculopapular skin lesions, oral ulcers and neuropsychiatric symptoms. She had elevated titers of anti-nuclear antibody (ANA), Anti-ds-DNA, anti-histone antibodies and complement levels. Serum coxsackie and cytomegalovirus (CMV) IgM tests were positive, as well. Magnetic resonance imaging (MRI) of the brain demonstrated extended cerebral and cerebellar atrophy. Pediatricians should be attentive to the possibility of neurolupus for patients with neurological problems despite a young age at presentation. Appropriate therapy is a challenging task.
Keywords: Neuropsychiatric lupus; Pediatrics; CMV; Coxsackie